2004
DOI: 10.1111/j.1551-2916.2004.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Habits of Grains in Dense Polycrystalline Solids

Abstract: We show here that the boundaries of individual grains in dense polycrystals prefer certain crystallographic habit planes, almost as if they were independent of the neighboring crystals. In MgO, SrTiO3, MgAl2O4, TiO2, and aluminum, the specific habit planes within the polycrystal correspond to the same planes that dominate the external growth forms and equilibrium shapes of isolated crystals of the same phase. The observations decrease the apparent complexity of interfacial networks and suggest that the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 24 publications
5
73
0
Order By: Relevance
“…It is known that there is a strong inverse correlation between the grain boundary energy and its population (i.e., the high energy planes have the minimum population and vice versa). [10][11][12] The energy of grain boundary can closely be correlated with the surface energy as they both imitate the local disruption in atomic bonds at the grain boundary interface. The surface energy anisotropy of Fe-3 pct Si was measured for a temperature range of 1273 K to 1673 K (1000°C to 1400°C) using a lattice harmonics series in conjunction with Fourier analysis technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that there is a strong inverse correlation between the grain boundary energy and its population (i.e., the high energy planes have the minimum population and vice versa). [10][11][12] The energy of grain boundary can closely be correlated with the surface energy as they both imitate the local disruption in atomic bonds at the grain boundary interface. The surface energy anisotropy of Fe-3 pct Si was measured for a temperature range of 1273 K to 1673 K (1000°C to 1400°C) using a lattice harmonics series in conjunction with Fourier analysis technique.…”
Section: Discussionmentioning
confidence: 99%
“…This unique procedure, which is described in detail elsewhere, [6] enables us to successfully measure the grain boundary plane orientation distribution along with the misorientation distribution. This technique was employed to survey the grain boundary plane distribution in different materials, such as Al, [9] SrTiO 3 , [10] TiO 2 , [11] MgAl 2 O 4 , [11] MgO [12] and determine the correlation between the grain boundary plane distribution and the grain boundary energy. These measurements generally revealed remarkable anisotropy in the distribution of grain boundary planes at a given lattice misorientation.…”
Section: Introductionmentioning
confidence: 99%
“…13, which compares free surface energies with grain boundary populations for MgO (cubic) [42][43][44], TiO 2 (rutile, tetragonal) [60], and Al 2 O 3 (corundum, trigonal) [61]. On average, rather than seeking high symmetry configurations, grain boundaries tend to favor configurations in which at least one side of the interface can be terminated by a low index plane [62]. Recall that the energy cost for making a grain boundary can be thought of as the energy to create the two surfaces on either side of the interface, minus the binding energy that is recovered by bringing the two surfaces together.…”
Section: Measurements Of Grain Boundary Energy Anisotropymentioning
confidence: 99%
“…The GBCD is the relative areas of grain boundaries distinguished by their lattice misorientations and grain boundary plane orientations. Results from experiment and simulation suggest that there is an inverse relationship between the relative energy of a grain boundary and its total area in the polycrystal [8,10,[22][23][24]. Measurements have shown that in SrTiO 3 the most common grain boundaries in the distribution are both more numerous and have larger average areas than others [25].…”
Section: Introductionmentioning
confidence: 99%